Японська зброя у зібранні Полтавського краєзнавчого музею імені Василя Кричевського - Кондратенко, Н.Г. (Сіверщина в історії України, 2023)
Стаття присвячена колекції японської холодної та вогнепальної зброї у зібранні Полтавського краєзнавчого музею імені Василя Кричевського. Збірка нараховує чотирнадцять одиниць – дванадцять зразків холодної зброї (нагамакі, таті, катана, вакідзасі, танто, айкуті, ярі) та дві одиниці вогнепальної (теппо, бадзе-дзутсу). Підвалини колекції було закладено ще на зорі діяльності музею наприкінці ХІХ – на початку ХХ ст. меценатом Павлом Бобровським. Кадровий військовий, що мандрував Єгиптом, країнами Близького і Далекого Сходу, передав до музею 2777 речей. Проте Друга світова війна завдала руйнівного удару по музейному зібранню. Лише тринадцять одиниць японської зброї із довоєнного зібрання пережили цей час, хоч і зазнали значних пошкоджень у ході евакуації до м. Уфа. Один із ножів надійшов до колекції вже після війни завдяки Ігорю Вауліну, який привіз його в якості сувеніра із Манчжурії. Наразі колекція досліджена, атрибутована та підготовлена до повноцінного введення в експозиційний простір. The article is dedicated to cold weapon and firearms in the Vasyl Krychevsky Poltava Local Lore Museum gathering. Collection includes fourteen items – twelve samples of cold weapon (nagamaki, tachi, katana, wakizashi, tanto, aikuchi, yari) and two ones of firearms (teppo, badzedzutsu). Basis of this collection was made by philanthropist Pavlo Bobrovskyi in the late 19th – early 20th century. As a career officer he traveled in Egypt, countries of Near and Far East and gave to the museum 2777 artifacts from those lands. Alas the Second World War made serious damage to the gathering. Only thirteen items of Japanese weapon from the pre-war collection survived, though they were rather harmed during evacuation to the Ufa City in the northern part of USSR. One of knives came to the collection in 1949 from Ihor Vaulin, who brought it from Manchuria. The most popular kind of weapon in Japan is obviously cold weapon that functioned through ages without serious evolutionary changes and became sociocultural phenomenon. There are eight swords in the Vasyl Krychevsky Poltava Local Lore Museum collection. They are nagamaki with beautiful handle decorated with mother of pearl, tachi with casing made of magnolia wood, elegant katana with still sharp blade and five wakizashi with various and tenuous elements. Knives in museum collection are represented with two tanto and aikuchi. One tanto is engraved with birds at the blade. The other one has beautiful wooden scabbard carved with sunflowers. Aikuchi impresses with ivory scabbard and handle decorated with mythological plot. The only spear belongs to yari type. Its shaft was lost during the Second World war, but blade illustrates this kind of cold weapon. Firearms are represented with rifle teppo and pistol badze-dzutsu. As firearms came late in Japan and was not so widespread before the late 19th century each sample is precious. Now collection is explored, attributed and made ready to complete implementation into exposition.